Database theory and application, bio-science and bio-technology International Conferences, DTA and BSBT 2011, Held as Part of the Future Generation Information Technology Conference, FGIT 2001 in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings - Kim, Tai-hoon; Adeli, Hojjat; Cuzzocrea, Alfredo; Arslan, Tughrul; Zhang, Yanchun; Ma, Jianhua; Chung, Kyo-il; Mariyam, Siti; Song, Xiaofeng (Communications in computer and information science, 2011)
This book comprises selected papers of the International Conferences, DTA and BSBT 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focuse on the various aspects of database theory and application, and bio-science and bio-technology.